2017
DOI: 10.1039/c7ra06447k
|View full text |Cite
|
Sign up to set email alerts
|

Novel highly stable β-cyclodextrin fullerene mixed valent Fe-metal framework for quick Fenton degradation of alizarin

Abstract: b-Cyclodextrin (b-CD) supported magnetic nanoscaled fullerene/Fe 3 O 4 (CDFMNPs) and fullerene/Fe 3 O 4 (FMNPs) composites were prepared and characterized. These composites can be utilized as heterogeneous catalysts for the Fenton oxidation reaction to degrade alizarin in aqueous solutions. The saturation magnetization (M s ) value of quasi-spherical CDFMNPs was found to be 13.16 emu g À1 and their diameter was in the range of 25-30 nm. The catalytic activities of the prepared materials were tested with varyin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 53 publications
1
10
1
Order By: Relevance
“…Importantly, a phenomenon may be noted from Figure c, showing that the homogeneous Fenton reaction conduces continuously even after 240 min in a strongly acidic condition. This result indicates that F-Z-C shows good stability and the functional substances (mainly cyclodextrin) on the material are not destroyed; this conjecture can also be confirmed in previous studies. , …”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…Importantly, a phenomenon may be noted from Figure c, showing that the homogeneous Fenton reaction conduces continuously even after 240 min in a strongly acidic condition. This result indicates that F-Z-C shows good stability and the functional substances (mainly cyclodextrin) on the material are not destroyed; this conjecture can also be confirmed in previous studies. , …”
Section: Resultssupporting
confidence: 85%
“…This result indicates that F-Z-C shows good stability and the functional substances (mainly cyclodextrin) on the material are not destroyed; this conjecture can also be confirmed in previous studies. 45,46 3.4. Concluded Mechanism of the F-Z-C Heterogeneous Fenton Reaction.…”
Section: Influence Of Initial Phmentioning
confidence: 99%
“…Good stability was found in five repeated runs. In a related study, fullerene/Fe 3 O 4 particles were coated with βCD (spherical particles of 25–30 nm) [203] . Catalyst features in the degradation of alizarin (entry 4), including total iron ion dissolution of 7 mg L −1 , are similar to those given in entry 3.…”
Section: Degradation Of Pollutantsmentioning
confidence: 71%
“…Note that • OH can interact with AR in different positions, i.e., can get close to AR from many directions, e.g., perpendicular to the aromatic ring; therefore, an adduct formation can be also an option for a radical scavenger. It is worth mentioning that under specific conditions, the complete degradation of alizarin could be detected, and the role of hydroxyl radical was taken into account in the proposed mechanisms [ 49 , 50 ].…”
Section: Resultsmentioning
confidence: 99%
“…In most computational studies about radical scavengers and their reactions to free radicals, the type of radical formation has been discussed; however, we have found that there is a lack of knowledge about the adduct formation of these well-investigated compounds [45][46][47][48]. It is worth mentioning that the degradation of alizarin has been also studied experimentally but only a few mechanistic studies could be found under specific conditions resulting in completely decomposed structures [49,50].…”
Section: Introductionmentioning
confidence: 99%